Addressing intimate partner violence during the COVID-19 pandemic and beyond: how radiologists can make a difference - Matoori, Simon Sam; Khurana, Bharti; Balcom, Marta Chadwick; Froehlich, Johannes M.; Janssen, Sonja; Forstner, Rosemarie; King, Ann D.; Koh, Dow-Mu; Gutzeit, Andreas (European radiology, 2021)
Faced with the COVID-19 pandemic, many countries both in Europe and across the world implemented strict stay-at-home orders. These measures helped to slow the spread of the coronavirus but also led to increased mental and physical health issues for the domestically confined population, including an increase in the occurrence of intimate partner violence (IPV) in many countries. IPV is defined as behavior that inflicts physical, psychological, or sexual harm within an intimate relationship. We believe that as radiologists, we can make a difference by being cognizant of this condition, raising an alert when appropriate and treating suspected victims with care and empathy. The aim of this Special Report is to raise awareness of IPV among radiologists and to suggest strategies by which to identify and support IPV victims.
Gesehen am 29.07.2021
Published online: 6 October 2020